Effect of pH on heat tolerance of hot spring diatom Achnanthidium exiguum AARL D025–2 in cultivation - Supattira Pruetiworanan (2018)
© 2017, Springer Science+Business Media Dordrecht. Diatoms have been recognized as a promising raw material for biodiesel production as a result of their thermal stability. However, potent thermotolerant strains of diatoms, such as hot spring diatoms, have not yet been studied. Achnanthidium exiguum AARL D025–2 was originally isolated from a habitat at temperatures ranging from 39 to 45 °C; however, it could only be isolated and maintained at 30 °C. Hence, it has been determined that certain factors have a considerable impact on the thermostability of this diatom. One factor that has not yet been given as much consideration is pH. The pH can be significant for the growing conditions and physiology of algal cells. Thus, this study aims to investigate the effect of pH on thermotolerant diatom cultivation. The diatom A. exiguum AARL D025–2 was cultivated in modified Bold Basal Medium at different pH (7.0, 8.0, 9.0, and 10.0) and at temperatures of 30, 40, and 50 °C. Growth was monitored by direct cell-counting, while fatty acid methyl ester (FAME) composition was also examined. The results showed that an alkaline pH could promote the heat tolerance of this diatom. The optimal culture conditions for biomass and FAME production was pH 9 at 40 °C. The major FAMEs were C16-C18, which may be suitable for the purposes of biodiesel production. The results from this research study will be useful for the future development of thermotolerant diatom cultivation with regard to the study and promotion of alternative energy sources.